Perceived Rigidity in Motion-in-Depth Increases with Contour Perspective. (June 2014) - Vienne, Cyril; Blondé, Laurent; Mamassian, Pascal
When observers are asked to match the depth of an object according to its height, they often report systematic errors depending on viewing distance. Systematic biases can also arise while vergence distances are induced by binocular disparities. Observers of stereoscopic images tend to overestimate the depth of objects displayed in front of the screen, while the depth of objects displayed behind the screen plane is underestimated. This phenomenon creates a serious problem in that veridicality in depth perception appears distorted when one attempts to render the metrics of a captured 3-D world. These distortions could also subsist with structure-from-motion information and during motion-in-depth. Observers judged the circularity of transparent rotating cylinders that were either static or moving in depth. Crossed results show that participants could precisely retrieve the best modulation between presented depth and width. As this effect could be amplified with stimuli containing stronger perspective cues (ie contour perspective), participants judged the rigidity of spinning cubes, moving along the line of sight, which were either edges-defined or defined by randomly textured surfaces (dots). The results showed that, although depth constancy was not improved by contour perspective, perceived rigidity was increased by perspective when the best scaling estimate was displayed. This finding suggests that appropriate binocular disparity information in combination to monocular signal is necessary for stereoscopic depth perception.